2012
DOI: 10.1111/j.1365-2702.2012.04117.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dietary and fluid non‐adherence in Jordanian patients with end‐stage renal disease receiving haemodialysis: a cross‐sectional study

Abstract: Identification of the factors that may worsen dietary and fluid non-adherence may lead to improved therapeutic interventions within the mainstream of medical practice for Jordanian patients with end-stage renal disease receiving haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 32 publications
5
67
4
4
Order By: Relevance
“…"Intake exceeds output" indicates that the intake of a quantity of liquid in the body is more than the amount eliminated (20) . A study found that adherence to diet control and fluid intake has no relationship with psychosocial predictors and the perception of health but is related to a set of factors that can influence patient compliance in the control of fluid intake, and the best indicators are not being recognised to predict this behaviour (29) . However, a restricted diet can promote distortions in its proper fulfilment.…”
Section: Discussionmentioning
confidence: 99%
“…"Intake exceeds output" indicates that the intake of a quantity of liquid in the body is more than the amount eliminated (20) . A study found that adherence to diet control and fluid intake has no relationship with psychosocial predictors and the perception of health but is related to a set of factors that can influence patient compliance in the control of fluid intake, and the best indicators are not being recognised to predict this behaviour (29) . However, a restricted diet can promote distortions in its proper fulfilment.…”
Section: Discussionmentioning
confidence: 99%
“…6.7% of Brazilian participants, 5.1% of Americans (2) and 5.7% of Hispanics were considered non-adherent to the medication. (18) Non-adherent to the diet were 14.1% of Brazilians, 12% of Americans and 19.2% of Hispanics. In the fluid intake domain, there were greater differences among the results found: 17.9% of non-adherent Brazilians, 10.34% of Americans and 5.7% of Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological and motivational aspects seem to play a prominent role in non-adherence to treatment. (18) In the hemodialysis domain, 85.8% considered it "extremely important" to follow the prescribed recommendation. On the other hand, 32% were considered non-adherent on the basis of objective criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Khalil ve ark.nın yapmış olduğu çalışmada hastaların çoğunluğu diyet ve sıvı kısıtlamasına uyum sağlamadıklarını saptamışlardır (30). Hastaların tedavi ve diyete uyumları bilgi, algı ve beceriye dayalı bir davranıştır.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified